Optimization of Container Dwell Time at Tanjung Perak Port, Indonesia: Container Flow Approach - Aditya Subur Purwana; Muhammad Anshar Syamsuddin; Ilham Majid (Lembaga Publikasi Ilmiah Nusantara, 2026)
Dwell Time (DT) is the waiting period required for an imported container, measured from the time the container is unloaded from a ship until it leaves the port area. Tanjung Perak Port, Indonesia's second-largest logistics hub, recorded a DT of 3.36 days in July 2025, exceeding the national target of 2.87 days. In July 2025, Tanjung Perak Port handled 53,446 import containers, representing 20.98% of the total import containers entering Indonesia's five main ports. This study aims to determine the optimal DT point at Tanjung Perak Port using quantitative econometric methods, specifically quadratic models and optimization. The study uses secondary data from January to September 2025, comprising 397,485 containers, which were analyzed using Stata 19 and Excel Solver. The results indicate that the minimum optimal DT at Tanjung Perak Port is 2.48 days. The time components consist of 1.24 days from stacking to job order (X1), 0.96 days from job order to gate-in (X2), and 0.28 days from truck gate-in to gate-out (X3). These findings suggest that the DT at Tanjung Perak Port can be further optimized to reach its minimum level. This study uses container flow as a proxy for goods movement; therefore, future research may incorporate both goods and document flows to provide a more comprehensive analysis.